Navigasi Perubahan dan Inovasi dalam Industri Penerbangan: Tinjauan Literatur Sistematis Tentang Kepemimpinan Transformasional: Made Adithya Dharma, Dhian Supardam - Made Adithya Dharma; Dhian Supardam (Jurnal Teknologi dan Manajemen Sistem Industri, 2024)
The study "Navigating Change and Innovation in the Aviation Industry: A Systematic Literature Review of Transformational Leadership" examines how transformational leadership influences change management and innovation within the aviation sector. By systematically reviewing existing literature, the research evaluates current knowledge and identifies gaps for further exploration. Key findings highlight the importance of transformational and inclusive leadership in enhancing job performance, satisfaction, and organizational commitment. Despite these insights, more research is required to explore the nuanced relationship between leadership styles and employee performance. The study offers valuable guidance for leaders and policymakers aiming to boost employee engagement and satisfaction through effective leadership. This work extends the understanding of transformational leadership with a specific emphasis on its application in the aviation industry.